Method Development and Validation of Short-Chain Brain Sulfatide Using RP-HPLC UV - Benin Joseph; Kalaichitra P; Bibhas Kar; Vishnupriya D; Muthulakshmi V (Asian Journal of Pharmaceutical Research and Development, 2026)
The main objective of this research is to present the development and validation of reverse- phase high-performance liquid chromatography RP-HPLC UV method for the determination of short-chain brain sulfatide. The method was performed on HPLC system (Waters, Alliance 2695, USA) equipped with Waters 2487 Dual Absorbance UV/Vis Detector. The column used for the method is Eximius C18 (250mm.L x 4.6mm I.D x 5um) with particle size 5µm and pore size of 100 Å with a guard column from Thermo Fisher Hypersil BDS C18 Guard 10x4mm 5um. The mobile Phase consists of solvent A, 100% methanol and solvent B, methanol: water (1:1, pH 3.5 formic acid) used at a ratio 90:10 (v/v). The flow rate was set at 0.700ml/min and the detection at 254nm. Linearity, precision, accuracy and recovery, specificity and robustness were the parameters validated as per ICH guidelines. The short-chain brain sulfatide’s retention time was found to be 3.9 minutes and linearity R2 value was found to be 0.97. The limit of detection (LOD) and the limit of quantification (LOQ) were determined to be115.66 ng/µl and 350.49 ng/µl. The %RSD value for recovery was found to be 2.06. The above findings reveal that this method is simple, precise and accurate method for short-chain brain sulfatide.